The Leadership Competencies Of Madrasah PrincipalIn Improving TheProcess Of Islamic Religious Learning - Mohammad Zaini (CV. Inara, 2021)
The function of the principal of madrasah as supervisor included some activities related to the awakening of the spirit, cooperation of teachers, the fulfillment of madrasah tools, the equipment for smooth learning, the development of the knowledge and some skills of teachers’ cooperation between madrasahs and the community. The aimed were to enhancing the quality of education and teaching the students. Therefore, in order to improving the effectiveness and efficiency in learning, the madrasah principal had double responsibility, those were: a) the madrasah administration, it created an enjoyable of learning situation, and b) doing the supervision. So, he could do a well job, it was guiding the students’ growth.